Chapter Introduction - Bennett, Audrey (Taylor & Francis, 2023)
Critical mapping-a problematizing, reflective approach to design inquiry-investigates how existing design outcomes (DOs) can be coupled to form a wicked solution to address a wicked problem. We have found that visual framing married to affinity organization is one of the most important strengths in critical mapping, helping to communicate the concepts to stakeholders, structure our analysis, and identify places to intervene in the system to design a more sustainable future. In this book, we apply critical mapping to the challenge of identifying and compiling food DOs that are equitable, just, and resilient against ecological and economic changes; that is, the wicked solution must entail sustainable design. "Sustainable design" in this context refers to the manifestation of creative problem solving across a range of intangible and tangible design forms of varying degrees of sustainability. Using food insecurity as the wicked problem, this chapter introduces a visual framework for critically mapping a wicked solution, a diagram onto which existing sustainable DOs are charted and analyzed to identify places where designers should intervene to impact the current state of the system-in the specific case of food-and shift it toward a future of sustainable food security within the realm of equity and justice.